Sudden cardiac death after coronary artery bypass graft surgery and role of antiplatelet therapy - Iftikhar Ali Ch; Azhar Chaudhry; Mishal Zehra; Pei-Tzu Wu; Mashal Tahirkheli; Poonam Bai; Ananya Bhaktaram; Rahat Jamal; Sabrina Chaudry; Faris Amil; John Randolph; Steven Miller; et al. (PLoS ONE, 2025)
Background While coronary artery bypass grafting (CABG) surgery is effective in reducing the risk of myocardial infarction and subsequent cardiac events by improving myocardial perfusion, the risk of sudden cardiac death (SCD) remains notable. Methods This retrospective observational study evaluated the efficacy of dual antiplatelet therapy (DAPT) in preventing sudden cardiac death (SCD) among patients undergoing CABG surgery at a major U.S. cardiac center (2012–2015). Data was manually extracted from electronic medical records between 23/04/2017 to 30/03/ 2018 and verified for accuracy, with patients categorized into DAPT or aspirin monotherapy groups based on discharge prescriptions. Results Of 2,476 patients followed in this post-CABG study, the analysis included 1,005 patients who received aspirin monotherapy (AMT) and 1,458 patients who received dual antiplatelet therapy (DAPT). AMT group had a significantly higher incidence of SCD compared to those on DAPT (3.1% vs 0.8%; OR = 3.831, 95% CI: 1.961–7.519; p < 0.001). The binary regression model indicated that a higher BMI was associated with an increased risk of SCD (HR = 1.064, 95% CI: 1.012–1.118, p = 0.014). However, patients prescribed P2Y12 antagonists (HR = 0.285, 95% CI: 0.135–0.603, p < 0.001), those with a GFR >  60 ml/min (HR = 0.314, 95% CI: 0.158–0.624, p < 0.001), and those with a higher ejection fraction (HR = 0.962, 95% CI: 0.939–0.986, p = 0.002) were less likely to experience SCD following CABG. A 1 kg/m2 increase in BMI is associated with a 6.4% increase in the risk of SCD. Morbidly obese patients with BMI >  35 were more likely to have experienced SCD than those with BMI < 35 (HR = 2.400, 95% CI: 1.204–4,787; p =  0.013). Similarly, patients with EF > 40% had decreased incidence of SCD compared to those with EF < 40% (HR 0.347, 95% CI:0.158–0.763; p = 0.008). Patients on AMT had higher all-cause (OR = 2.136, 95% CI 1.502–3.038; p < 0.001) and CV mortality (OR = 3.731, 95% CI 2.233–6.235; p < 0.001) but had lower incidence of major bleeding (by drop in hemoglobin criteria) (OR = 0.704, 95% CI: 0.595–0.833; p < 0.001) compared to the DAPT group. Conclusion DAPT prescription after CABG improves survival and lowers risk of sudden cardiac death.